Comparative Analysis of the Editorial Use of Generative Artificial Intelligence in Journalism Education: A Case Study - Mateos-Abarca, Juan Pablo; Sedano Rodríguez, Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This research focuses, through the analysis of a contextual review of artificial intelligence (AI) in the media sector and a case study, on how future media professionals use these tools, as well as on assessing their effectiveness and reliability. The approach of the study is based on a comparative analysis between the production of news headlines by journalism students and headlines produced by an intelligent editorial assistant. To carry out the analysis, a group of 80 students brought together, who produced two headlines for a written report they had previously prepared. In the first phase of the process, the students generated a headline with their own reflective process. In the second phase, they created another headline option using an assistant from generative artificial intelligence. The research shows that artificial intelligence creates headlines faster than the students and, moreover, with greater efficiency in all five variables analyzed.